Generalized Cantor Set and its Fractal Dimension (Bangladesh Journal of Scientific and Industrial Research, 2012)
Keywords: Cantor sect; fractal; fractal dimension; box-counting dimensionDOI: http://dx.doi.org/10.3329/bjsir.v46i4.9598BJSIR 2011; 46(4): 499-506